Wolbachia Natural Infection of Mosquitoes in French Guiana: Prevalence, Distribution, and Genotyping - Emmanuelle Clervil; Amandine Guidez; Stanislas Talaga; Romuald Carinci; Pascal Gaborit; Anne Lavergne; Sourakhata Tirera; Jean-Bernard Duchemin (Microorganisms)
Wolbachia are the most spread bacterial endosymbionts in the world. These bacteria can manipulate host reproduction or block virus transmission in mosquitoes. For this reason, Wolbachia-based strategies for vector control are seriously considered or have already been applied in several countries around the world. In South America, Wolbachia have been studied in human pathogen vectors such as sand flies and mosquitoes. In French Guiana, the diversity and distribution of Wolbachia are not well known in mosquitoes. In this study, we screened for Wolbachia natural infection in mosquitoes in French Guiana by using 16S rRNA, Wolbachia surface protein (WSP), and multi-locus sequence typing (MLST) molecular assays. A total of 29 out of 44 (65.9%) mosquito species were positive for natural Wolbachia infection according to the PCR results, and two Wolbachia strains co-infected three specimens of Mansonia titillans. Then, we analyzed the phylogenetic relationships among the Wolbachia detected. All of the tested specimens of Aedes aegypti, the major dengue vector of French Guiana, were negative. These results regarding Wolbachia strain, distribution, and prevalence in mosquitoes from French Guiana highlight Wolbachia–mosquito associations and pave the way for a future Wolbachia-based strategy for vector control in this Amazonian territory.